Migrant Community Participation in a Mega Sporting Event: New Zealand Chinese and the Rugby World Cup 2011 - Lau, Chloe (Auckland University of Technology, 2015)
In addition to economic, cultural and social impacts, mega sporting events also provide a host country with a legitimate approach to promote national identities and cultures on a global scale. As the largest event ever staged in New Zealand, the nation’s Government believed that the Rugby World Cup 2011 would generate these benefits for the host population. Building social cohesion by engaging New Zealanders in the event was one of the four major event goals. However, the event’s “uniquely New Zealand” thumbprint slogan may create doubts of national identity for some members in the local ethnic communities who are not devotees of rugby. Through a proposed stakeholder framework, a case study of the Chinese migrant community in Auckland explores the relationships inherent in their participation: their awareness of the event and its connection to event participation, economic links, and identity and pride. The changes in participation of local Chinese as players and supporters of rugby, national relationship, identity and pride, multicultural value, linkage to New Zealand, and intention to recommend New Zealand are analysed. Previous research on event stakeholder relationships neglects the possible multiple roles played by the host community. This relative neglect also extends to the variance in importance and dominance of individual event stakeholder groups. Various modes of stakeholder participation in a temporal dimension is another omission in event research. In particular, existing literature about community participation in mega sporting events is relatively scarce. Host communities’ various subgroups and their complexities also represent research gaps to be filled. The research shows that the entire hosting community is involved in a range of elements of the event being undertaken: planning, organising, producing, managing, participating, and marketing and evaluating. Adopting a triangulation approach incorporating content analysis, in-depth interviews, and questionnaires, this case study develops an event stimulation model with appropriate strategies to enhance awareness and encourage participation of host community stakeholders. A six-month Web audit adopting a macro-analytic content-analysis approach first looks at the event’s temporal dimension using both quantitative and qualitative methods. Through dendrogram analyses, key informant in-depth interviews are used to gain greater insight into the activities that were conducted and planned by various event stakeholders in the local Chinese community before the Rugby World Cup 2011. A pre- then post-event questionnaire survey targeting local Chinese, and which combined face-to-face and online elements, was then conducted to understand the relationship of different research themes. Five hundred and two self-administered questionnaires and 385 online questionnaires from the pre-event survey and 503 self-administered and 146 online questionnaires for the post-event survey were collected and examined with multivariate analysis. The findings indicate that mega-event awareness may not simply translate into “mega” participation. A stakeholder relationship map is developed which features redefined groupings of event stakeholders and proposed modes of participation in a mega sporting event. Active participation in a mega sporting event has multidirectional branching out effects to stimulate positive impact on identity and pride, multicultural value, linkage to the country, recommendation of the country, and business engagement. An event stimulation model is developed with five attributes: build ownership, identify stakeholders, manage expectations, capture participation, and leverage from the participation effect. To optimise positive social impact, it is recommended that the event planner considers an event stimulation strategy that factors in the temporal dimension.
Keywords: Mega event; Rugby World Cup; Sporting event; New Zealand; Migrant; Participation